Are we there yet? On a journey towards more contextually relevant resources in speech-language therapy and audiology - Michelle Pascoe; Christine Rogers; Vivienne Norman (South African Journal of Communication Disorders, 2013)
Audiologists and speech-language therapists working in developing contexts like South Africa have the opportunity to address a range of needs through their research. One of these needs is the development of assessments and therapy materials that are appropriate for their clients’particular language needs and cultural background. This editorial paper aims to introduce original research in speech-language therapy and audiology, which has been carried out in South Africa and other developing contexts and is presented in this volume of the journal. In addition we suggest that while the focus of much research is on the destination or end product that is developed, there is a need to share the methodologies that are used to reach that goal so that more research can be carried out by a wider pool of students, researchers and clinicians. We describe some of the methods that we have used in our research – often in small scale projects with budgetary constraints, which would be feasible for clinicians in their routine clinical contexts. Our hope is that others can build on these approaches, critique and share their own strategies for the ultimate advancement of the professions in southern Africa.